Rwandan Collaborative Model for Educator Capacity Building - Andrew Moore; Vincentie Nyangoma; Jaco Du Toit; Peter Wallet; Pascal Rukundo (Journal of Systemics, Cybernetics and Informatics, 2018)

(untitled)
Collaboration between the Rwandan government, the University of Rwanda, and local industry to develop and deploy educator technology-integration professional development initiatives neatly follows the Triple Helix Model[1]. However, in this Rwandan initiative a fourth collaborative partner proved significant, the regional/global education community coordinated by UNESCO's Regional Office for Eastern Africa. The ICT Essentials for Teachers' Course was designed to exploit a blended-learning methodology, developed using Open Educational Resources and deployed by locally trained online facilitators. This paper presents a model of how effective collaboration between stakeholders can result in the quick and cost-effective development and deployment of educator training initiatives that are scalable.